Autoregulation in Resistance Training for Lower Limb Tendinopathy: A Potential Method for Addressing Individual Factors, Intervention Issues, and Inadequate Outcomes - Burton, Ian (Frontiers in Physiology, 2021)
Musculoskeletal disorders such as tendinopathy are having an increasing burden on society and health systems. Tendinopathy is responsible for up to 30% of musculoskeletal disorders, having a high incidence in athletes and the general population. Although resistance training has shown short-term effectiveness for treating lower limb tendinopathy, more comprehensive exercise protocols and progression methods are required due to poor long-term outcomes. The most common resistance training protocols are pre-determined and standardised, which presents significant limitations. Current standardized protocols do not adhere to scientific resistance training principles and do not consider individual factors or take the importance of individualised training into account. Resistance training programs in tendinopathy are currently not achieving required intensity and dosage, leading to high recurrence rates. Therefore, better methods for individualising and progressing resistance training are required to improve outcomes. One potential method is autoregulation, which allows individuals to progress training at their own rate, taking individual factors into account. Despite being found effective for increasing strength in healthy athletes, autoregulation methods have not been investigated in tendinopathy. The purpose of this narrative review was threefold: first to give an overview and critical analysis of individual factors involved in tendinopathy and current resistance training protocols and their limitations. Secondly, to give an overview of the history, methods and application of autoregulation strategies both in sports performance and physiotherapy. Finally, a theoretical adaptation of a current tendinopathy resistance training protocol with autoregulation methods is presented, providing an example of how the method could be implemented in clinical practice or future research.